Traumatic inferior lumbar hernia. Issue 5 (27th May 2022) - Baig, Niyaz; Elberm, Hassan; Warren, Patrick
Abstract: Traumatic lumbar hernias are rare, with little surgical literature describing their management. In this we report about a 41-year-old patient admitted to University Hospital Southampton following a high velocity road traffic collision, of estimated speed 140 mph. He suffered multiple bony injuries, and a traumatic right inferior lumbar hernia containing the ascending colon. The hernia was surgically repaired extra-peritoneally with mesh and abdominal wall muscles approximated and sutured.